A framework to integrate game engine in the learning management system - Wan Mohd Amir Fazamin Wan Hamzah (Fakulti Sains dan Teknologi, 2012)
Educational computer games (ECGs) present an appealing environment that engage students in activities which deliver substantive educational content. It can aid the development of proficiency by allowing users to interact with objects and manipulate variables.